GC-MS Metabolomic Profiling of Protic Metabolites Following Heptafluorobutyl Chloroformate Mediated Dispersive Liquid Microextraction Sample Preparation Protocol - Hušek, Petr; Švagera, Zdeněk; Hanzlíková, Dagmar; Karlínová, Iva; Řimnáčová, Lucie; Zahradníčková, Helena; Šimek, Petr (Methods in molecular biology (Clifton, N.J.), 2018)
A simple analytical workflow is described for gas chromatographic-mass spectrometry (GC-MS)-based metabolomic profiling of protic metabolites, particularly amino-carboxylic species in biological matrices. The sample preparation is carried out directly in aqueous samples and uses simultaneous in situ heptafluorobutyl chloroformate (HFBCF) derivatization and dispersive liquid-liquid microextraction (DLLME), followed by GC-MS analysis in single-ion monitoring (SIM) mode. The protocol involves ten simple pipetting steps and provides quantitative analysis of 132 metabolites by using two internal standards. A comment on each analytical step and explaining notes are provided with particular attention to the GC-MS analysis of 112 physiological metabolites in human urine.
Keywords: formiáty; Formates; Dispersive liquid-liquid microextraction; biologické markery; Quantitative analysis; Biomarkers; Metabolomic profiling; Urinalysis; lidé; mikroextrakce kapalné fáze; Metabolomics; Liquid Phase Microextraction; GC-MS; Fluorocarbons; metabolomika; plynová chromatografie s hmotnostně spektrometrickou detekcí; analýza moči; Chloroformate derivatization; Gas Chromatography-Mass Spectrometry; fluorokarbony; Urine; Humans